Poor protective potential of influenza nucleoprotein antibodies despite wide prevalence. Issue 1 (9th November 2021) - Vanderven, Hillary A; Esterbauer, Robyn; Jegaskanda, Sinthujan; Tan, Hyon‐Xhi; Wheatley, Adam K; Kent, Stephen J
Abstract: Humans are exposed to influenza virus through periodic infections. Due to these repeated exposures, human populations commonly have elevated antibody titers targeting the conserved internal influenza virus nucleoprotein (NP). Despite the presence of anti‐NP antibodies, humans are acutely susceptible to drifted influenza viruses with antigenically different surface proteins and the protective potential of human NP antibodies is unclear. In this study, high levels of anti‐NP antibody and NP‐specific B cells were detected in both adult humans and influenza‐infected mice, confirming that NP is a major target of humoral immunity. Through sorting single B cells from influenza‐exposed human adults, we generated a panel of 11 anti‐NP monoclonal antibodies (mAbs). The majority of anti‐NP human mAbs generated were capable of engaging cellular Fc receptors and bound NP on the surface of influenza‐infected cell lines in vitro, suggesting that anti‐NP mAbs have the potential to mediate downstream Fc effector functions such as antibody‐dependent cellular cytotoxicity and antibody‐dependent phagocytosis. However, human anti‐NP mAbs were not protective in vivo when passively transferred into a murine influenza challenge model. Future in vivo studies examining the synergistic effect of anti‐NP mAbs infused with other influenza‐specific mAbs are warranted. Abstract : Due to repeated exposures, human populations commonly have elevated antibody titers targeting the conserved internal influenza virus nucleoprotein (NP). Through sorting single B cells from influenza‐exposed human adults, we generated a panel of 11 anti‐NP monoclonal antibodies (mAbs). Most of the anti‐NP human mAbs generated were capable ofengaging cellular Fc receptors and bound NP on the surface of influenza‐infected cell lines, but the anti‐NP mAbs were not protective in vivo when passively transferred into a murine influenza challenge model.